2013
DOI: 10.1186/1471-230x-13-31
|View full text |Cite
|
Sign up to set email alerts
|

Threaded biliary inside stents are a safe and effective therapeutic option in cases of malignant hilar obstruction

Abstract: BackgroundAlthough endoscopic biliary stents have been accepted as part of palliative therapy for cases of malignant hilar obstruction, the optimal endoscopic management regime remains controversial. In this study, we evaluated the safety and efficacy of placing a threaded stent above the sphincter of Oddi (threaded inside plastic stents, threaded PS) and compared the results with those of other stent types.MethodsPatients with malignant hilar obstruction, including those requiring biliary drainage for stent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 32 publications
1
58
0
Order By: Relevance
“…Endoscopic sphincterotomy for above stent placement becomes obsolete even if multiple stents are planned 15 . For the maintenance of the above stent device, there are sometimes difficulties in its retrieval; however, a string can be attached to this device to overcome this concern 15 16 30 . The above stent device can be easily removed and reduces the risk of cholangitis.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic sphincterotomy for above stent placement becomes obsolete even if multiple stents are planned 15 . For the maintenance of the above stent device, there are sometimes difficulties in its retrieval; however, a string can be attached to this device to overcome this concern 15 16 30 . The above stent device can be easily removed and reduces the risk of cholangitis.…”
Section: Discussionmentioning
confidence: 99%
“…14 Moreover, in a retrospective study on humans by Inatomi et al, suprapapillary PS placement had more favorable outcomes than transpapillary PS placement (median patency period: 142 for iPSs vs. 32 for transpapillary PSs, p=0.04 on log rank test). 10 This is the first study evaluating outcomes of suprapapillary PS versus suprapapillary MS placement. However, three retrospective studies of iPS without comparison to MS reported median patency periods of 136 days, 9 142 days, 10 and 190 days.…”
Section: Discussionmentioning
confidence: 99%
“…10 This is the first study evaluating outcomes of suprapapillary PS versus suprapapillary MS placement. However, three retrospective studies of iPS without comparison to MS reported median patency periods of 136 days, 9 142 days, 10 and 190 days. 8 In our study, iPSs had significantly longer median patency periods with no unfavorable outcomes in terms of clinical efficacy, short-and long-term adverse events, or survival period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 , 27 , 28 In addition, reflux of duodenal content into the biliary tract may be a contributing factor, as prior studies have shown that positioning above the papilla/sphincter of Oddi may improve patency for both plastic and metallic prostheses. 29 , 30 , 31 , 32 In addition, those required surgical tumor debulking had shorter stent patency at multivariate analysis, perhaps due to inflammatory chemokines produced by the tumor. 33 …”
Section: Discussionmentioning
confidence: 99%